Design, synthesis, and insecticidal activity of a novel series of flupyrimin analogs bearing 1-aryl-1H-pyrazol-4-yl subunits - Zhao, Fenghai; Tang, Xianjun; Huang, Jiaxing; Li, Jiaqi; Xiao, Yumei; Qin, Zhaohai (Frontiers in Chemistry, 2022)
To discover new potential insecticides to protect agricultural crops from damage, a series of novel flupyrimin derivatives containing an arylpyrazole core were designed and synthesized. Their structures were confirmed by 1H NMR, 13C NMR, and HRMS. Bioassays indicated that the 31 compounds synthesized possessed excellent insecticidal activity against Plutella xylostella. Among these target compounds, the lethality of A3, B1-B6, D4, and D6 reached 100% at 400 μg/ml. Moreover, when the concentration dropped to 25 μg/ml, the insecticidal activities against the Plutella xylostella for compounds B2, B3, and B4 still reached more than 70%. The structure–activity relationship of the Plutella xylostella was discussed. The density functional theory analysis of flupyrimin and B4 was carried out to support the abovementioned structure–activity relationship. The possible binding modes between receptor and active groups in title compounds were also verified by docking simulation. These results provided new ideas for the development of these novel candidate insecticides in the future.